Pengembangan media e-catalog bahan pangan lokal dalam pengolahan dry product - Dian Ashari, Aprilia; Ika Wahyu Kusuma Wati; Sri Wahyu Andayani; Susetyo, Eko; Syafiq, Abdullah (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to develop an e-catalog of local foodstuff in the processing of dry products, determine the feasibility of learning media, and student responses. This type of research is development & research which uses the Four-D development model consisting of defining, designing, developing, and disseminating. The subjects of this study were students who took copyrighted works courses as many as 32 respondents. The e-catalog media feasibility assessment was carried out by material experts, media experts, and responses from students. The instrument used was a questionnaire with descriptive statistical data analysis techniques. Research Results: 1) Development of e-catalog media for local food ingredients in dry product processing adapting 4 stages namely a) definition stage, b) design stage, c) development stage, and d) dissemination stage; 2) The developed learning media is very suitable for use based on material experts with a percentage of 100% (very feasible), while media experts with a percentage of 97.5% (very feasible); and 3) Student response to e-catalog media for local food ingredients in dry product processing in a small-scale trial with 10 respondents getting a percentage of 87.13% (very feasible), while a large-scale trial with 22 respondents with a percentage of 88.97% (very feasible). This shows that the e-catalog of local food ingredients in the processing of dry products in copyright courses can be used as a learning medium in the learning process.